Heavier element-containing aromatics of [4n+2]-electron systems - Ota, Kei (2022)
While the implication of the aromaticity concept has been dramatically expanded to date since its emergence in 1865, the classical [4n+2]/4n-electron counting protocol still plays an essential role in evaluating the aromatic nature of compounds. Over the last few decades, a variety of heavier heterocycles featuring the formal [4n+2] π-electron arrangements have been developed, which allows for assessing their aromatic nature. In this review, we present recent developments of the [4n+2]-electron systems of heavier heterocycles involving group 13-15 elements. The synthesis, spectroscopic data, structural parameters, computational data, and reactivity are introduced.